2018
DOI: 10.12659/msm.909682
|View full text |Cite|
|
Sign up to set email alerts
|

Evodiamine Induces Apoptosis, G2/M Cell Cycle Arrest, and Inhibition of Cell Migration and Invasion in Human Osteosarcoma Cells via Raf/MEK/ERK Signalling Pathway

Abstract: BackgroundOsteosarcoma is a prevalent type of bone tumor mainly reported in children and adolescents. The treatments for osteosarcoma are limited and are associated with serious adverse effects. In this study we evaluated the anticancer activity of Evodiamine, a plant-derived natural product, against a panel of osteosarcoma cells and explored the underlying mechanisms.Material/MethodsThe viability of osteosarcoma cell lines was investigated by MTT assay. Apoptosis was detected by DAPI and annexin V/PI staining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…encoded cell cycle regulatory protein that participated in regulating G2/M progression and mediating DNA damage repair. It has been reported that Evodiamine, Flavokawain B and Ludartin could inhibit proliferation, migration, and apoptosis of osteosarcoma cells by down-regulating the expression level of CDC25C [62][63][64] . At present, the relationship between the rest of hub genes (DTL, CENPN, PARPBP, SMC2) and osteosarcoma remains unclear and the speci c role in lung metastasis deserves further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…encoded cell cycle regulatory protein that participated in regulating G2/M progression and mediating DNA damage repair. It has been reported that Evodiamine, Flavokawain B and Ludartin could inhibit proliferation, migration, and apoptosis of osteosarcoma cells by down-regulating the expression level of CDC25C [62][63][64] . At present, the relationship between the rest of hub genes (DTL, CENPN, PARPBP, SMC2) and osteosarcoma remains unclear and the speci c role in lung metastasis deserves further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Evodiamine was shown to inhibit the proliferation of human osteosarcoma 143B02 cells through inactivation of PTEN/PI3K/Akt pathway [ 154 ]. By inactivating Raf/MEK/ERK signaling pathway, evodiamine also induced growth inhibition and inactivated the activities of migration and invasion of U2OS cells [ 155 , 156 ]. Moreover, the inactivation of Wnt/β-catenin signaling pathway contributed to the cytotoxic activity of evodiamine in human osteosarcoma MG-63 cells [ 157 ].…”
Section: Pharmacological Activitymentioning
confidence: 99%
“…Many studies suggested that RAF can affect the proliferation of cell through in uencing the distribution of cell cycle [29][30][31], and we speculated that the signi cant and rapid change of estradiol level was caused by GCs proliferation. Our ow cytometry analysis results showed that RAF709 did not induce the suppression of cell cycle stage, but affected on the activity of estradiol synthase, which con rmed that RAF1 could regulate the expression of CYP19A1 [32] through the ERK signaling pathways [33].…”
Section: Discussionmentioning
confidence: 92%